A Systematic Review of the ARGRA Model for Technology-Based Reading Diagnosis in Elementary Education - Ita Kurnia; Alfi Laila; Saktian (JURNAL PENDIDIKAN DASAR NUSANTARA, 2026)
Accurate reading assessment is fundamental to elementary school literacy development. The ARGRA model (Adaptive Reading Assessment, Readability Analysis, Gamification, and Android-Based Assessment) addressed the static nature and poor engagement of conventional testing. Following PRISMA 2020 guidelines, a systematic review was conducted across six databases (2009—2025). Out of 38 full-text articles assessed, 30 independent empirical studies (reported across 37 papers) met inclution criteria. Methodological quality was evaluated using the Newcastle Ottawa Scale (NOS), categorizing 78% of studies as high quality. Results demonstrate a morderate to strong association between ARGRA components and reading diagnosis accuracy (r = 0.41, 95% CI [0.35, 0.47]). Computerized Adaptive Testing (CAT) yielded the highest unique effect (r = 0.52), followed by readability formulas (r = 0.44), gamification r = 0.38), and Android platforms (r = 0.35). gamification significantly elevated student engagement, although its direct effect on diagnostic score accuracy varied based on game mechanics. Furthermore, intervention trials showed a combined transfer effect size of Hedges g = 0.31. these findings confirm that integrating adaptive item selection, readability targeting, and mobile delivery establishes a scalable, evidence-based diagnostic framework for early literacy intervention.